Production Network Knowledge as A Foundation for Resistance ‐ Workers Influence on A Chinese Acquisition in Germany. (13th November 2015) - Bollhorn, Kai; Franz, Martin
Abstract: This paper analyses how workers in Germany's automotive industry developed power in the process of a transnational carve out – namely the carve‐out of the rubber and plastics department of the German automotive supplier ZF Friedrichshafen AG to the Chinese based Zhuzhou Times New Material Technology Co., Ltd. in 2013. The worker's actions were successful because they used their production network knowledge and decided against a strategy of pure co‐operative co‐determination but implemented a strategy of resistance. They concentrated their resistance on the weak points within the value creation processes of the automotive production network. On the basis of this, the authors argue that production network knowledge can be used to develop collective power within organisations. The study is based on qualitative interviews with ZF observing participation of workers events and a press analyses on the particular acquisition.